The Effect of Core Stabilization Training (Six Weeks) on Falling Rate in Elderly Female - Soolmaz Mahdavi; Masud Golpaigani; Nader Shavandi; Amin Farzaneh Hessari; Rahman Sheikh Hoseini (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The purpose of this study was to examine the effect of core stabilization Abstract training program on falling in elderly population. Methods & Materials: For this clinical trial study, forty elderly female subject (age: 70.58±5.98 years, weight: 55.76±5.78 kg, height: 157.76±7.8 cm) voluntarily participated. A week prior to starting training program the balance measured with the Berg Balance Test (BBT) and subjects divided into two groups, based on obtained score in BBT low risk falling (group 1), high risk falling (group 2) groups. Then subjects divided to two control & Experimental groups. The Experimental groups performed a core stabilization program included three levels for 6- week and three times per week on the alternate day and 30 min in section. The post-test of BBT were done for two groups afterwards. Independent and dependent t-test used to analyze the data. Significant level Considered to be %0.05. Results: In group 1&2 no Significant differences shown for pretest of balance between control & experimental groups (P=0.486, P=0.193). The balance of experimental groups compared to control groups improved after training program (P=0.007, P=0.000). Rate of improvement in experimental groups 1 and 2 were 3.38% and 15/06% and fore control groups were 0.95% and 3.7% respectively. Conclusion: Core stabilization training program may improve balance and decrease falling in elderly.